2016
DOI: 10.1016/j.bioelechem.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various sterilization procedures on TiO2 nanotubes used for biomedical devices

Abstract: Sterilization is the final surface treatment procedure of all implantable devices and is one of the key factors which have to be considered before implementation. Since different sterilization procedures for all implantable devices influence mechanical properties as well as biological response, the influence of different sterilization techniques on titanium nanotubes was studied. Commonly used sterilization techniques such as autoclaving, ultra-violet light sterilization, hydrogen peroxide plasma sterilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Significant changes were observed after autoclaving, whereby TNTs structures (15, 50, 100 nm in diameter) were damaged to some extent at both the top and bottom.Severe destruction was observed on smaller diameter TNTs, where the open mouth of TNT collapsed while the bottom delaminated. However, the different sterilization methods did not influence the wettability of freshly prepared and sterilized TNTs[57]. Interestingly, in this study only freshly fabricated TNTs were used, as it was reported that ageing turns TNTs more hydrophobic within three weeks[58].…”
mentioning
confidence: 76%
“…Significant changes were observed after autoclaving, whereby TNTs structures (15, 50, 100 nm in diameter) were damaged to some extent at both the top and bottom.Severe destruction was observed on smaller diameter TNTs, where the open mouth of TNT collapsed while the bottom delaminated. However, the different sterilization methods did not influence the wettability of freshly prepared and sterilized TNTs[57]. Interestingly, in this study only freshly fabricated TNTs were used, as it was reported that ageing turns TNTs more hydrophobic within three weeks[58].…”
mentioning
confidence: 76%
“…31 For instance, with increasing of the annealing temperature, the concentration of the cell-toxic electrolyte residualfluorine decreases. 24,27 In our previous studies, we also proved the long-term hydrophilicity of the annealed TiO 2 NTs, 28 in comparison with the less-hydrophilic amorphous TiO 2 NTs and hydrophobic Ti foil. 27 Despite the unaltered structure of the TiO 2 NT after annealing, TiO 2 NTs' surface with anatase crystal structure prepared in the present study do not provide an environment suitable for platelet adhesion and activation, which is from the view point of stent application beneficial, as it could prevent platelet aggregation and blood clot formation, i.e., thrombosis.…”
Section: Disscussionmentioning
confidence: 54%
“…The TiO 2 NTs were fabricated by the electrochemical anodization method, as described in the literature 24,25 with the Voltcraft VSP 2653/VSP 2206 laboratory power supply. Experiments were carried out at room temperature (» 20°C) in a two-electrode system (Pt/Ti foils) with a working distance of 15 mm.…”
Section: Synthesis Of Tio2 Nts By Electrochemical Anodizationmentioning
confidence: 99%
“…Sterilization is usually the final surface treatment procedure of all implantable devices and it also must be considered before implementation. Different sterilization procedures for all implantable devices can influence mechanical properties and biological responses [ 146 , 147 , 148 ]. Junkar et al [ 148 ] investigated the effect of different sterilization techniques (sterilization with autoclave, sterilization with ultra-violet (UV) light radiations, commercial hydrogen peroxide (H 2 O 2 ) plasma, and oxygen plasma treatment) on titanium dioxide nanotubes (TiO 2 NTs).…”
Section: Surface Texture-based Surface Treatments With Improved Pementioning
confidence: 99%